Evaluation of patient-related factors and index treatment in recurrent ingrown toenail cases (Annals of Medical Research, 2025)
Aim: This study aims to evaluate patient-related factors and previous treatments in patients with ingrown toenails that subsequently recurred. In this context, recommendations for clinical practice are proposed to contribute to the development of both effective treatment methods and preventive strategies.Materials and Methods: This retrospective study included 42 patients previously treated for ingrown toenails who developed recurrences due to various reasons. Patients with post-treatment complications (e.g., infection and bleeding), pain associated with the treatment, or dissatisfaction with the treatment were not considered as a recurrence and were excluded from the study. All patients gave informed consent for participation in the study. The demographic characteristics such as age and gender, patient-related factors that might affect recurrence (foot hygiene, footwear usage, nail trimming, additional deformities, trauma history, comorbidities), the clinics where the initial treatment was performed, and the initial treatment methods were recorded.Results: The mean age of the patients was 26.8 ± 10.1 years, with the youngest being 12.0 years and the oldest 49.0 years. Of the patients, 33.3% (n=14) were female, and 66.7% (n=28) were male. Comorbidities included diabetes mellitus in 21.4% (n=9), obesity in 31.0% (n=13), peripheral arterial disease in 7.1% (n=3), and hyperhidrosis in 16.7% (n=7). No predisposing factors were identified in 11.9% (n=5) of the 42 patients. An evaluation of initial treatment methods revealed that 40.5% (n=17) of the patients underwent Orthonyxia, 21.4% (n=9) underwent Chemical Partial Matricectomy, 21.4% (n=9) underwent Spicule Excision, and 16.7% (n=7) underwent Partial Matricectomy.Conclusion: Ingrown toenails are common in the general population and can significantly impair quality of life. When left untreated or improperly treated, they may result in unexpected and troublesome outcomes. Reducing risk factors and receiving appropriate treatment from an experienced clinician will help lower recurrence rates.
Keywords: Ingrown toenail; Recurrence; Index treatment; Partial matricectomy; Nail trimming